2022
DOI: 10.1111/exd.14674
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cutaneous bacterial microbiota of Thai patients with seborrheic dermatitis

Abstract: Seborrheic dermatitis (SD) is a chronic inflammatory skin condition that occurs in body areas that contain profuse sebaceous glands. Skin microbiota are diverse across ethnic groups and its dysbiosis has been implicated in the pathogenesis of SD. Here, we reported the contribution of cutaneous bacterial microbiota to SD in the Thai population. Healthy individuals and patients with scalp SD were recruited into the study. Normal skin, scalp skin lesion (SL) and non‐lesion sites (SNL) samples were collected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Previous studies in atopic dermatitis patients demonstrated a clear staphylocidal effect and decreased microbial dysbiosis compared to the placebo with doses as low as 1% once or twice daily [ 23 , 24 ]. Involvement of Staphylococcus , and especially S. aureus , in the pathophysiology of atopic dermatitis has gained attention [ 6 , 7 ], and microbial profiling studies in SD have shown increased Staphylococcus abundances, accordingly [ 5 , 31 , 32 , 33 ]. However, this might not necessarily constitute dysbiosis as these studies have shown similar [ 32 , 33 ] or higher [ 31 ] biodiversity indexes compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in atopic dermatitis patients demonstrated a clear staphylocidal effect and decreased microbial dysbiosis compared to the placebo with doses as low as 1% once or twice daily [ 23 , 24 ]. Involvement of Staphylococcus , and especially S. aureus , in the pathophysiology of atopic dermatitis has gained attention [ 6 , 7 ], and microbial profiling studies in SD have shown increased Staphylococcus abundances, accordingly [ 5 , 31 , 32 , 33 ]. However, this might not necessarily constitute dysbiosis as these studies have shown similar [ 32 , 33 ] or higher [ 31 ] biodiversity indexes compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of Staphylococcus , and especially S. aureus , in the pathophysiology of atopic dermatitis has gained attention [ 6 , 7 ], and microbial profiling studies in SD have shown increased Staphylococcus abundances, accordingly [ 5 , 31 , 32 , 33 ]. However, this might not necessarily constitute dysbiosis as these studies have shown similar [ 32 , 33 ] or higher [ 31 ] biodiversity indexes compared to healthy controls. Moreover, this study was limited by insufficient phylogenetic resolution, which does not enable differentiation between S. aureus and S. epidermidis that are regarded as pathobiont and commensal species, respectively [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification of the 16S rRNA gene at the V3-V5 region was performed using the universal prokaryotic primers 342F (5′-GGRGGCAGCAGTNGGGAA-3′) and 895R (5′-TGCGDCCGTACTCCCCA-3′) with appended barcode and adaptor sequences ( Human Microbiome Project (HMP) Consortium, 2012a ; Castelino et al, 2017 ; Wongsaroj et al, 2021 ; Dityen et al, 2022 ). The 342F was used elsewhere and the 895R position was shared with the 909R.…”
Section: Methodsmentioning
confidence: 99%
“…The 342F was used elsewhere and the 895R position was shared with the 909R. The in-silico analysis revealed that the V3-V5 primers could identify bacteria on phylum/class/order/family levels with >77% efficiency, genus 56.6% and species 21.1% ( Wang & Qian, 2009 ; Human Microbiome Project (HMP) Consortium, 2012a ; Castelino et al, 2017 ; Johnson et al, 2019 ; Darwish et al, 2021 ; Suwarsa et al, 2021 ; Wongsaroj et al, 2021 ; Dityen et al, 2022 ). Each PCR reaction comprised 1 × EmeraldAmp GT PCR Master Mix (TaKaRa, Shiga, Japan), 0.2 μM of each primer, and 50–100 ng of the genomic DNA in a total volume of 75 µL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation